The influence of the duration of in vitro maturation and incubation with an activating agent on the hatching capacity of bovine parthenotes - Orozco-Lucero, Ernesto (2020)
The period of both in vitro maturation (IVM) and incubation with oocyte activators affects the blastocyst yield following parthenogenetic activation (PA). Nevertheless, it is still unknown how these conditions impact the expansion and hatching rates of bovine parthenogenetic blastocysts. The objective of this study was to assess the influence of the duration of IVM and exposure to the activating agent, 6-dimethylaminopurine (6-DMAP), on a number of developmental parameters in bovine parthenotes, including: Cleavage, blastocyst formation, expansion, and hatching. Slaughterhouse oocytes were subjected to different periods of IVM. Subsequently, eggs were first parthenogenetically activated for five minutes with ionomycin and then incubated for distinct lengths of time with a second activator, 6-DMAP. The treatments were: a) Control: 22 h IVM/4 h 6-DMAP; b) 22 h IVM/5 h 6-DMAP; c) 24 h IVM/4 h 6-DMAP; and d) 24 h IVM/5 h 6-DMAP. Developmental stages were evaluated at day 4 and day 8 of in vitro culture (IVC). No differences were detected in most developmental parameters. However, the duration of IVM and incubation with 6-DMAP significantly affected (P<0.05) hatching capacity considering the number of blastocysts (Hatch./Blast.). Also, this same variable was higher (P<0.05) in group b) 22 h IVM/5 h 6-DMAP (45.89 ± 12.59%), as compared to c) 24 h IVM/4 h 6-DMAP (6.67 ± 6.67%). In conclusion, the length of IVM and incubation with 6-DMAP influenced parthenogenetic development, where 22 h IVM/5 h 6-DMAP was the condition producing the highest Hatch./Blast. rate in bovine parthenotes.